1985
DOI: 10.1084/jem.161.5.1237
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow function. I. Peripheral T cells are responsible for the increased auto-antiidiotype response of older mice.

Abstract: Recently (1) we have shown that, with age, there are changes in B cell clonal expression as manifested by differences in the idiotypes (Id) produced and an increase in the magnitude of the auto-anti-Id response. The increased auto-antiId response can be transferred to young recipients with splenic lymphoid cells from aged animals (2). However, lethally irradiated mice reconstituted with bone marrow (BM) from aged donors behave like young mice in that they manifest only modest auto-anti-Id responses (2), sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…These data were consistent with the hypothesis that long-lived peripheral T cells serve as a repository for memory of life-long interactions with self and environmental antigens and that these peripheral T cells shift the clonal distribution of B cells arising from the bone marrow. These conclusions, initially derived from cell-transfer studies, have been confirmed in experiments with the autoreconstituted mouse model (5).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…These data were consistent with the hypothesis that long-lived peripheral T cells serve as a repository for memory of life-long interactions with self and environmental antigens and that these peripheral T cells shift the clonal distribution of B cells arising from the bone marrow. These conclusions, initially derived from cell-transfer studies, have been confirmed in experiments with the autoreconstituted mouse model (5).…”
Section: Discussionsupporting
confidence: 54%
“…It appears that the age-associated changes in these characteristics of the primary immune response of old animals to antigen are determined by the peripheral T-cell population. We have obtained (5) evidence that hapten-augmentable PFCs are cells whose secretion of antibody is reversibly inhibited by the binding of anti-Id autoantibody to cell surface immunoglobulin. If the curves for hapten inhibition of plaque formation are calculated from the maximum number of PFCs detected in the presence of low concentrations of hapten rather than from the number of PFCs in the absence of hapten, then one can estimate the avidity distribution of the total population of TNP-specific B cells, including those whose secretion had been inhibited by the binding of anti-Id autoantibody.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Szewczuk and Campbell (1980) have also found evidence for a strong influ ence of anti-Id antibodies on B-cell respon siveness in old mice. Generation of these regulatory, anti-idiotypic antibodies seems to depend on the presence of T cells from old mice, in that animals allowed to reconstitute their own immune systems from protected limb bone marrow after ir radiation produce such antibodies only if inoculated with T cells from old mice dur ing the repopulation interval (Kim et al, 1985); the presence of aged T cells during the period of autoreconstitution also leads to mice that, like old controls, produce antibodies of lower affinity and higher IgM/IgG ratios (Tsuda, Kim, Siskind, & Weksler, 1988).…”
Section: B Lymphocytesmentioning
confidence: 97%
“…and bone marrow reconstituted the periphery together with T cells from young or aged donors. It was found that mice that received young T cells displayed auto-anti-idiotypic antibody profiles and a response to TNP-F like that of the young donor (61,62), whereas those that received aged T cells responded like the aged donors (61,62). These results strongly implicate the T cells in the quantity and quality of the immune response.…”
Section: Bone Marrow and Agingmentioning
confidence: 65%